LEGAL PROTECTION FOR FOREIGN WORKERS IN THE CASE OF UNILATERAL TERMINATION OF EMPLOYMENT BEFORE THE END OF THE EMPLOYMENT PERIOD - Desi Lestari Lubis; Muhamad Abas; Yuniar Rahmatiar; Tatang Targana (Jurnal Ilmiah Advokasi, 2024)
The state holds constitutional responsibility in the field of labor by providing legal protection to ensure legal certainty for individuals involved, particularly in the context of employing foreign labor. However, such protection applies only to foreign workers who meet the legal standing requirements in Indonesia. This research addresses the case of unilateral termination of employment against Stephane Baudoin by PT Origin Resort Lombok. Utilizing a normative juridical method, the findings indicate Baudoin's entitlement to legal recourse due to fulfilling the criteria of legal standing in labor matters. The appellate decision of the Supreme Court confirms PT Origin Resort Lombok's violation of the Job Creation Law. This study aims to contribute to the literature on the protection of foreign workers, focusing on industrial relations disputes and legal safeguards. Keywords: Foreign Workers, Industrial Relations Disputes, Legal Protection